Design and Synthesis of a Class of Compounds That Inhibit the Growth of Fungi Which Cause Invasive Infections. Issue 3 (20th January 2020) - Nakada‐Motokawa, Nana; Miyazaki, Taiga; Mizuta, Satoshi; Tanaka, Yoshimasa; Hirayama, Tatsuro; Takazono, Takahiro; Saijo, Tomomi; Yamamoto, Kazuko; Imamura, Yoshifumi; Izumikawa, Koichi; Yanagihara, Katsunori; Makimura, Koichi; et al.
Abstract: Invasive fungal infections are growing causes of morbidity and mortality in immunocompromised patients. However, only one antifungal drug class has been developed in the last 30 years, extremely limiting current therapeutic options. To address unmet medical needs, we performed high‐throughput screening of 9600 chemical compounds and identified an aminohydrazone derivative as a novel and potent antifungal compound. We then designed and synthesized a series of aminohydrazone derivatives, and demonstrated that 1‐[( E )‐[4‐(3′, 4′‐dichlorobenxyloxy)phenyl methylidene]amino]‐guanidine had the most potent inhibitory activity and exhibited a broad spectrum of antifungal activities against Candida species (including multidrug resistant C. auris ), Aspergillus species, Cryptococcus neoformans, and Rhizopus oryzae . Against C. albicans, the leading cause of Candida infections, the compound had fungicidal activity for planktonic cells at 8 μg mL −1 (25 μM) and anti‐biofilm activity at 34 μg mL −1 (100 μM). This study provides new insights for the development of a new drug class for the treatment of invasive fungal infections which are often refractory to conventional therapies. Abstract : The compound 1‐[( E )‐[4‐(3′, 4′‐dichlorobenxyloxy)phenyl methylidene]amino]‐guanidine belongs to a novel class of antifungals and its fungicidal activities against Candida albicans are equivalent or superior to those of conventional drugs on a weight‐per‐volume basis. In addition, the newly synthesized compound inhibited the growth of Candida auris NCPF 8985, a multidrug‐resistant strain of Candida species.